2020
DOI: 10.1038/s41598-020-59160-7
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery-related complications in patients with end-stage renal disease- a nationwide population-based study in Taiwan

Abstract: this nationwide retrospective case-control study was aimed at elucidating the risk from cataract surgery in end-stage renal disease (ESRD) patients. Cataract surgery patients were identified using the diagnostic and procedural codes for International Classification of Diseases, 9 th Revision, Clinical Modification from Taiwan's National Health Insurance Research Database. ESRD patients were selected as cases, while propensity scores for age, sex, comorbidities and year-of-surgery-matched patients without chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The National Health Insurance (NHI) program is a single-payer, compulsory, universal health insurance plan established on March 1, 1995 that covers all forms of health care services for more than 99% of Taiwan’s 23.5 million residents 23 , 24 . The National Health Insurance Research Database (NHIRD) included comprehensive medical data, including records of registration, ambulatory and inpatient care, catastrophic illnesses, and drug prescriptions 23 27 . Patient identification numbers and other sensitive personal data have been encrypted in NHIRD to protect individual privacy 27 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Health Insurance (NHI) program is a single-payer, compulsory, universal health insurance plan established on March 1, 1995 that covers all forms of health care services for more than 99% of Taiwan’s 23.5 million residents 23 , 24 . The National Health Insurance Research Database (NHIRD) included comprehensive medical data, including records of registration, ambulatory and inpatient care, catastrophic illnesses, and drug prescriptions 23 27 . Patient identification numbers and other sensitive personal data have been encrypted in NHIRD to protect individual privacy 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The National Health Insurance Research Database (NHIRD) included comprehensive medical data, including records of registration, ambulatory and inpatient care, catastrophic illnesses, and drug prescriptions 23 27 . Patient identification numbers and other sensitive personal data have been encrypted in NHIRD to protect individual privacy 27 . This study used data from the Longitudinal Health Insurance Database 2000 (LHID 2000), which is a subset of the NHIRD.…”
Section: Methodsmentioning
confidence: 99%
“…Many reports have demonstrated that, for patients with end-stage renal disease (ESRD), the risk of cataract [ 2 ], as well as postoperative complications, is significantly higher [ 3 , 4 , 5 , 6 , 7 ]. The first retrospective case–control study that undertook a risk assessment of cataract surgery in patients with ESRD was reported in 2020 [ 8 ]. The study covered 352 cases and 1760 controls who underwent cataract-removal surgery between 2002 and 2013 in Taiwan.…”
Section: Introductionmentioning
confidence: 99%